MUNGKINKAH BUDAYA ORGANISASI BERUBAH? - Brigita Meylianti Sulungbudi (Center for Economic Studies Universitas Katolik Parahyangan, 2001)
The organization’s culture develops from its leadership, but also. The culture of an organization en affect the development of its leadership. Effective organizations require both tactical and strategic thinking as well as culture building by its leaders. Strategic thinking helps to create and build vision. The culture is the setting within which the vision take hold. At last, the vision may also determine the characteristic of the organization’s culture.